Explaining the Dignity of Humanity Based on the Anthropology of Muslim Philosophers - Sayyid ʿAbd al-Ra’ūf Afḍalī (آموزه‌‌های فلسفه اسلامي, 2024)
There is no doubt that humans are beings of dignity; however, there is disagreement about what dignity is and what its origin is. Some have referred to individuals’ social status as dignity or its origin, while others have mentioned resembling God or possessing reason (intellect). The concept of dignity based on the Islamic philosophical doctrines is a type of secondary intelligible (Arabic: مَعْقولُ الْثَّانی, romanized: maʿqūl al-thānī) and its origin of abstraction is the capacities of the rational (reasonable) soul (Arabic: اَلْنَّفْسُ الْنَّاطِقَة). The question is, does the rational soul possess the necessary capacities for the abstraction of dignity, and what are those capacities? We have demonstrated in this paper in an analytical-descriptive manner that the rational soul, from the perspective of Islamic philosophy, possesses extraordinarily complex capacities. In addition to having vegetative and animal capacities, it also possesses other capacities that aid it in the path towards angelic transformation. These capacities have caused Muslim philosophers to describe human beings with dignity and the like in various places of their works. From the perspective of Islamic philosophy, firstly, human beings possess dignity. Furthermore, the source of dignity is the entirety of the capacities of the rational soul. In addition, dignity is an inherent and universal matter. Lastly, dignity is a concept that can be understood in gradation and does not apply equally in all cases. Familiarity with the factors that strengthen human dignity, as well as an understanding of the challenges and obstacles to human dignity, is another outcome of this writing.